Recent advances in quantitative methods in cancer and human health risk assessment - Edler Lutz; Kitsos Christos P (New Jersey John Wiley, 2005)
Recent Advances in Quantitative Methods in Cancer and Human Health Risk Assessmentis a comprehensive text that accounts for the wealth of new biological data as well as new biological, toxicological, and medical approaches adopted in risk assessment. It
Keywords: Cancer; Cancer-risk factors-mathematical models; Mathematical modeling; Risk assessment